Characterization of tumor suppressive function of cornulin in esophageal squamous cell carcinoma. - Kai Chen; Yan Li; Yongdong Dai; Jiangchao Li; Yanru Qin; Yinghui Zhu; Tingting Zeng; Xiaojiao Ban; Li Fu; Xin-Yuan Guan (PLoS ONE, 2013)
By using cDNA microarray analysis, we identified cornulin (CRNN) gene was frequently downregulated in esophageal squamous cell carcinoma (ESCC). In the present study, we investigated the role of CRNN in ESCC development. The results showed that CRNN was frequently downregulated in primary ESCCs in both mRNA level (26/56, 46.4%) and protein level (137/249, 55%), which was significantly associated with lymph node metastases (P=0.027), advanced clinical stage (P=0.039), and overall survival rate (P<0.001). Multivariate analysis indicated that the CRNN downregulation was an independent prognostic factor for ESCC. Functional studies with both in vitro and in vivo assays demonstrated that CRNN had strong tumor suppressive ability in ESCC cells. The tumor-suppressive mechanism of CRNN was associated with its role in cell cycle arrest at G1/S checkpoint by upregulating expressions of P21(WAF1/CIP1) and Rb. Silencing CRNN expression by RNA interference could effectively inhibit its tumor suppressive effect. In conclusion, our findings demonstrate that CRNN is a tumor suppressor gene that plays a critical tumor suppressive role in ESCC.